Implementation of Local Wisdom-Based e-Module on Ecosystem Concepts to Enhance Elementary School Students' Environmental Awareness - Jaenudin, Dadang; Nurhayati, Nunung; Sukmanasa, Elly (Jurnal Penelitian dan Pembelajaran IPA, 2025)
Environmental awareness among elementary students is essential for fostering sustainable behaviors from an early age. This study aimed to investigate the effectiveness of local wisdom-based e-module on ecosystem concepts in enhancing environmental awareness among fifth-grade students. The research was conducted at a private elementary school in Bogor, Indonesia, involving 30 students through a quasi-experimental design with a one-group pretest-posttest model. The developed e-module integrated traditional ecological knowledge and local cultural values from the Bogor community, such as nature conservation, the sustainable use of resources, and ecosystem preservation. Results revealed a significant improvement in students’ environmental awareness, with an average pretest score of 52 and a posttest score of 58 out of a maximum of 64. The normalized gain (N-Gain) was 0.55, indicating a moderate level of effectiveness. Among six measured indicators, the highest gain was observed in “appreciating nature and ecosystems” (N-Gain = 0.73), while the lowest was in “participating in conservation efforts” (N-Gain = 0.20). These findings highlight the potential of integrating local wisdom into digital learning materials to strengthen character education and environmental values in primary education. Future research is recommended to incorporate community-based conservation activities for more comprehensive learning outcomes.